Pleistocene Bryozoans from the Clyde Clay Formation of Scotland, and the Holocene Retreat of Cold-Water Species - Paul David Taylor (Taxonomy, 2021)
Although bryozoans are a diverse phylum of aquatic invertebrates with a rich fossil record, very little has been written about bryozoan faunas from the latest Pleistocene at a time of rapid global change when temperatures increased dramatically and the sea-level rose. Two species of cyclostome and eight species of cheilostome bryozoans are here described from the late Devensian Clyde Clay Formation of Greenock, Scotland, based on historical material in the collections of the NHM, UK. All are illustrated for the first time from this deposit using scanning electron microscopy. Three of the species (Tubulipora cf. marisalbi, Rhamphostomella radiatula and Schizomavella porifera) are unknown from the seas around Scotland at the present-day but occur in colder waters to the north. This is consistent with the poleward retreat of cold-water species as seawater temperatures increased at the end of the Pleistocene.